2007
DOI: 10.1093/hmg/ddm060
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MMP-2 disrupts skeletal and craniofacial development and results in decreased bone mineralization, joint erosion and defects in osteoblast and osteoclast growth

Abstract: The 'vanishing bone' or inherited osteolysis/arthritis syndromes represent a heterogeneous group of skeletal disorders characterized by mineralization defects of affected bones and joints. Differing in anatomical distribution, severity and associated syndromic features, gene identification in each 'vanishing bone' disorder should provide unique insights into genetic/molecular pathways contributing to the overall control of skeletal growth and development. We previously described and then demonstrated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
201
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(219 citation statements)
references
References 53 publications
14
201
3
1
Order By: Relevance
“…Regardless of the exact mechanism, this study confirms previous reports that germ-line deletion of MMP-2 and separately MMP-9 causes reduced BMD (11,35) and reduced bone length, (6) respectively; and it further extends these changes to differential effects on the biomechanical, architectural, and compositional properties of bone. Of course, these effects could arise from the absence of these MMPs in chondrocytes during endochondral bone formation, but the persistence of the phenotype at 16 weeks of age, when bone remodeling and modeling are active, suggests that these MMPs are important to the organization of bone matrix with sufficient quality.…”
Section: Mmp2supporting
confidence: 90%
See 2 more Smart Citations
“…Regardless of the exact mechanism, this study confirms previous reports that germ-line deletion of MMP-2 and separately MMP-9 causes reduced BMD (11,35) and reduced bone length, (6) respectively; and it further extends these changes to differential effects on the biomechanical, architectural, and compositional properties of bone. Of course, these effects could arise from the absence of these MMPs in chondrocytes during endochondral bone formation, but the persistence of the phenotype at 16 weeks of age, when bone remodeling and modeling are active, suggests that these MMPs are important to the organization of bone matrix with sufficient quality.…”
Section: Mmp2supporting
confidence: 90%
“…(6,34) MMP-2, on the other hand, is expressed primarily by osteoblasts and plays a yet to be fully understood role in canaliculi formation. (11,35) Specifically, Mmp2 À/À bones display a . Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of MMP2 has been attributed to decreased mineralization and defects in the growth of osteoblasts and osteoclasts. 47 MMP2 has also been implicated as a negative regulator of chondrogeneis.…”
Section: Proteasesmentioning
confidence: 99%
“…The collagen degrading properties of MT1-MMP include both a direct collagenolytic activity and the ability to activate proMMP-2, the proform of the secreted gelatinase MMP-2 (4,(7)(8)(9), but the relative importance of these activities remains elusive. Mutations in the human MMP-2 gene give rise to severe bone disorders (10) and although ablation of the gene in mice was initially reported only to result in minor growth impairments (11), detailed analyses have revealed that MMP-2-deficient mice share many of the characteristics of the human disease in an attenuated form (12,13). In mice expressing a mutated collagen, modified in the classical collagenase cleavage site, concomitant MMP-2 deficiency was shown to severely impact skeletal development (14).…”
mentioning
confidence: 99%